Aurora-A V57I (rs1047972) polymorphism and cancer susceptibility: a meta-analysis involving 27,269 subjects. - Weifeng Tang; Hao Qiu; Heping Jiang; Lixin Wang; Bin Sun; Haiyong Gu (PLoS ONE)
Background The association between Aurora-A V57I (rs1047972, G>A) polymorphism and cancer susceptibility has been widely studied. However, the results are inconsistent. Methodology/principal findings To obtain a more precise evaluation of the relationship, we performed a meta-analysis of 14 case-control studies involving a total of 11,245 cancer cases and 16,024 controls. Our results demonstrated that there was a borderline evidence of an association between the Aurora-A V57I polymorphism and the decreased risk of overall cancer in two genetic models: AA vs. GA+GG and AA vs. GG. In a stratified analysis by cancer type, significant association between Aurora-A V57I polymorphism and the decreased risk of breast cancer was identified in one genetic model: AA vs. GG. In a stratified analysis by ethnicity, in three genetic models, significant decreased cancer risk was observed among Caucasians (AA vs. GA+GG; AA vs. GG and A vs. G) instead of Asians. Furthermore, a stratified analysis by ethnicity in breast cancer subgroup, five genetic models (AA+GA vs. GG; AA vs. GA+GG; AA vs. GG; AA vs. GA and A vs. G), significant decreased cancer risk was observed among Caucasians, but not among Asians. A slight publication bias was observed in our meta-analysis, thus nonparametric "trim-and-fill" method was utilized to detect the stability of our results. The adjusted odds ratios and confidence intervals showed that Aurora-A V57I polymorphism might be a protective factor for cancer risk, suggesting the reliability of our findings. Conclusion In summary, this meta-analysis suggests that Aurora-A V57I polymorphism may be a protective factor for cancer risk.